Determinants of choice for pigeons and humans on concurrent-chains schedules of reinforcement - Belke, T. W.; Pierce, W. D.; Powell, Russell A. (My University, 1989)
Demonstrated that the determinants of choice and preference are different for pigeons and humans exposed to the same concurrent schedules of reinforcement. Four male pigeons and 4 male undergraduates replicated E. Fantino's (see record 1970-03386-001 ) experiment that manipulated initial-link duration to test the divergent predictions of the delay-reproduction and reinforcement-density equations. Condition 1 exposed Ss to VI 90-sec and 30-sec initial links. Conditions 2 and 3 arranged equal initial-link schedules of 40 sec or 120 sec. Pigeons strongly preferred the alternative with the shorter terminal-link time to reinforcement, while delay-reduction equations did not predict the performance of humans in the unequal initial-link.
Keywords: choice behavior; concurrent reinforcement schedules; preferences; task complexity; pigeons; species differences; animals; choice behavior; Columbidae; humans; male; models, psychological; reinforcement (psychology); reinforcement schedule; time factors